When Wood Cladding Degenerates: Lessons on durability from traditional wood claddings after long weathering in real conditions - Brun, Géraldine (FormAkademisk, 2023)
For several decades, the mechanisms of deterioration of wood exposed outdoors have been scrutinized to ameliorate the performance of this versatile material when used for purposes such as house cladding. The performance of cladding seems to depend highly on the durability of wood, in turn connected to water uptake, which can vary greatly. How long a cladding can function is particularly complicated to define because of its paradoxical role as a sacrificial and aesthetic layer. However, thanks to reparations and maintenance, many traditional claddings are still preserved. They have been produced and maintained with local resources and show that low-processed wood can be durable in outdoor conditions. The contrast with modern approaches, such as wood modification or importation of durable species, raises the question: what durability of wood is concretely required for cladding purposes? The exhibition shows characteristics of wood weathered for up to hundreds of years, facilitating an understanding of the impact damage can have on the performance of cladding. The samples, issued from traditional French and Scandinavian facades, illustrate how exposure level influences degradation, confirming the role of rot and revealing the ones of erosion and abrasion in the degeneration of wood cladding. Both Alder and Pine seem to have the potential to perform naturally well as cladding for longer than it takes for the trees to regenerate. Traditions might teach us how to use local wood in a durable way if we consider biodegradation as an opportunity to build without creating waste, rather than as a threat.